The art of metal clay [videorecording] : techniques for creating jewelry and decorative objects - Haab, Sherri, author (New York : Watson-Guptill Publications, 2010)
Developed in Japan in the 1990s, metal clay consists of microscopic particles of silver or gold suspended in a pliable organic binder that can be worked with the hands and simple household tools. This book offers a comprehensive introduction to the medium designed specifically for crafters and jewelrymakers